Analisis efisiensi operasional bank muamalat indonesia: kajian rasio bopo periode 2020–2024 - Ariwibowo, Yusuf Ageng; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to understand how Bank Muamalat Indonesia maintains its operational efficiency by measuring the Operating Expenses to Operating Income (BOPO) ratio. This ratio not only reflects financial performance but also reflects how the bank manages resources, responds to industry dynamics, and strategizes to remain competitive amidst economic challenges. Using the latest published financial report data, this study examines the development of BOPO descriptively to identify improvements, obstacles, and factors influencing changes in the ratio. The results indicate that Bank Muamalat has demonstrated consistent efforts to improve efficiency, despite still facing operational cost pressures and the need to strengthen revenue sources. These findings are expected to provide a foundation for management in formulating more adaptive and sustainable strategies to improve the bank's performance.